Analisis Perjanjian Waralaba (Franchise) Kopi Kenangan Berdasarkan Peraturan Perundang – Undangan Tentang Waralaba - Anastasia Regita Rintan Sahara; Urbanisasi Urbanisasi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Franchising basically implies a settlement on techniques for deploying labor and products to customers. for this situation the franchisor licenses the franchisee to complete the exercise of conveying labor and products under the franchisor's name and attributes in selective territories, where the business is conducted simultaneously using the methodologies and strategies set by the franchisor and the franchisor provides assistance to the franchisee. This research was conducted using a statute approach. The regulation is based on the efforts of public authorities to energize the increase of establishment organizations throughout Indonesia with the aim of empowering public business people, especially small and medium business visionaries to develop as public franchisors in order to market domestic products. The agreement made by PT Kopi Kenangan with PT Sahara Group gave birth to an Agreement containing the agreement of the parties to bind themselves in the franchise agreement which is based on Government Regulation No. 42 of 2007 concerning Franchising.